ANALISIS PELAPORAN KEUANGAN DI YAYASAN AS-SALAM MANADO (BERDASARKAN PSAK 45 DAN PSAK 101) - ., Wahyuningsih; Karamoy, Herman; Afandy, Dhullo (Universitas Sam Ratulangi, 2018)
The financial statements are important media in the process of making economic decisions. There are several rules on the preparation of financial statements, one of which is the financial statements for non-profit entities and sharia entities. The purpose of this study is to analyze Financial Reporting As-Salam Manado Foundation in accordance with the concept of financial statements based on PSAK 45 and PSAK 101. In this study the type of data used is qualitative data, while for data sources using primary data and secondary data, the analytical method used is descriptive analysis. Based on the result of the research, it is concluded that the recording and presentation of the foundation's financial statements are still not in accordance with the applicable regulations, which are PSAK 45 and PSAK 101.Keywords: Non-profit Financial Statements